FORM OF ERROR USE OF THE WORD IN SEMANTIC STUDY ON BANNERS IN TANAH GARAM VILLAGE LUBUK SIKARAH DISTRICT SOLOK CITY - Elan - Halid (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
Language errors are when a person uses a language differently from how that language is supposed to be used. The word